Wedding planner in a box - Peraganathan, Megalah; Aman, Hannani; Mohd Yunus, Mohd Amin; Mustapha, Aida (Penerbit UTHM, 2017)
Marriage describes the connection of two souls who promise to become one heart. Everyone dreams their marriage to be nearly perfect and that will happen only if they are able to make their wedding plan with best packages. In this busy world, many couples delay their wedding mainly because of high budget required to meet their dream wedding ceremony. Wedding ceremony requires careful and meticulous planning from many aspects such as choosing the food, make up, decoration, and gifts.